The relationship between tax and economic growth: A South African perspective - Riba, Lerato (Research of GSB, 2017)
The purpose of this study is to investigate the impact of taxes in general and across the major three tax types, PIT, CIT and VAT on economic growth in South Africa. South Africa faces critically low growth levels amidst other challenges of high unemployment levels and significant inequalities. Government has a role of intervening in the economy through provision of public goods and services promoting economic development. This is facilitated through the levying of taxes. With the current concerns around tax policy and imminent tax increases in South Africa, it is imperative that a causal relationship between taxes and growth be investigated. The study covers the period 2003 to 2016, employing the ARDL framework to establish a long run relationship between taxes and growth at aggregate tax level, as well as major tax type level, where the model specified is derived from the GDP aggregate income approach. Results obtained indicate a long run equilibrium only at tax type level. This is followed by the Granger causality test that supports a demand-following hypothesis of growth over taxes in aggregate and PIT and CIT in particular, as well as a bi-directional relationship between growth and VAT, considered and indirect tax, consistent with the supply-leading hypothesis of consumption over growth. The results thus suggest that a positive relationship exists between taxes and growth where increases in tax lead to increases in growth in the VAT instance, then in the instance of increases in PIT and CIT, a result of increases in growth. It is recommended the Davis Tax Commission consider an increase in VAT rather than in the other tax types so as to bring about a more impactful, positive increase in economic growth, in alignment to the NDP.